The Value of Net Obscurity: Google Books and Unmediated Texts (Journal on Excellence in College Teaching, 2024)
Recent literary practices such as surface reading or the digital humanities have challenged the centrality of close reading in literary studies. Nonetheless, reading literature still involves sustained and productive attentiveness to texts. Fostering this skill, however, can seem increasingly difficult. From paper mills, to SparkNotes, to blogs and wikis, Google provides readings and key quotations for most any text on a college syllabus. This essay describes how instructors who value interpretive self-reliance may turn Google to their advantage. In a Victorian Gothic literature course and a general education literature course taken by non-majors, students compared depictions of the wind harp in Romantic and mid-18th-century poems. In both cases, students had to rely on their own analytic skills for the unmediated text, which generated more individual conversations, whole class discussion, and, most importantly, varied and textually specific responses than my previous assignments. Ways are suggested in which instructors can show students how to use Google Books effectively for their advanced research projects, which puts millennials' predilection for Google to productive use.